The Tim-3-Galectin-9 Pathway and Its Regulatory Mechanisms in Human Breast Cancer - Yasinska, Inna M.; Sakhnevych, Svetlana S.; Pavlova, Ludmila; Teo Hansen Selnø, Anette; Teuscher Abeleira, Ana Maria; Benlaouer, Ouafa; Gonçalves Silva, Isabel; Mosimann, Marianne; Varani, Luca; Bardelli, Marco; Hussain, Rohanah; Siligardi, Giuliano; et al. (Frontiers in Immunology, 2019)
Human cancer cells operate a variety of effective molecular and signalling mechanisms which allow them to escape host immune surveillance and thus progress the disease. We have recently reported that the immune receptor Tim-3 and its natural ligand galectin-9 are involved in the immune escape of human acute myeloid leukaemia cells. These cells use the neuronal receptor latrophilin 1 (LPHN1) and its ligand fibronectin leucine rich transmembrane protein 3 (FLRT3, and possibly other ligands) to trigger the pathway. We hypothesised that the Tim-3-galectin-9 pathway may be involved in the immune escape of cancer cells of different origins. We found that studied breast tumours expressed significantly higher levels of both galectin-9 and Tim-3 compared to healthy breast tissues of the same patients and that these proteins were co-localised. Increased levels of LPHN2 and expressions of LPHN3 as well as FLRT3 were also detected in breast tumour cells. Activation of this pathway facilitated the translocation of galectin-9 onto the tumour cell surface, however no secretion of galectin-9 by tumour cells was observed. Surface-based galectin-9 was able to protect breast carcinoma cells against cytotoxic T cell-induced death. Furthermore, we found that cell lines from brain, colorectal, kidney, blood/mast cell, liver, prostate, lung and skin cancers expressed detectable amounts of both Tim-3 and galectin-9 proteins. The majority of cell lines expressed one of the LPHN isoforms and FLRT3. We conclude that the Tim-3-galectin-9 pathway is operated by a wide range of human cancer cells and is possibly involved in prevention of anti-tumour immunity.